O dispositivo coletiva de imprensa na operação lava jato: estudo das estratégias estabelecidas por fontes, assessores e jornalistas - Anjos, Manoel Moabis Pereira dos (Universidade do Vale do Rio dos Sinos, 2021)
The thesis discusses the approaches that mark the contact between sources and journalists in the press conferences of the Lava Jato operation. The debate considers the press conference as an interactional device, that is, a space that is not necessarily physical where the participants resolve demands originated by their interests. The theoretical conduct of the work deals with the construction of mediation of that place by journalism as something related to the measures taken in the investigation processes. Among the elements of this investigation that are discussed in this work are plurality, a verification of the relationship with the sources in addition to organizational constraints. The methodological arrangement of the research considers three main axes: systematization of the recordings of the Lava Jato press conferences, face-to-face monitoring of environments and included with the participants. Seven episodes of interaction are mobilized to present how this device operates: Condução coercitiva do ex-presidente Lula; Defesa das 10 Medidas contra corrupção eleitoral; Troca de Delegados da Polícia Federal; Coletiva de imprensa do Power Point; Antecipação de deflagração de fase para o então Ministro Alexandre Moraes; Polícia Federal impossibilitada de realizar acordos de Delação Premiada e Explicação da não liberação de Lula para o velório do irmão Vavá. The episodes will be explored in a descriptive and reflective way. The focus of this selection is on materializing which hypotheses are representative to demonstrate the logic found in the interaction, journalist and source in the Press Conference device of the Lava Jato operation.
Keywords: Jornalismo; Entrevista coletiva; Fontes; Processos de apuração; Assessoria de imprensa; Journalism; Press conference; Sources; Counting processes; Press relations; ACCNPQ::Ciências Sociais Aplicadas::Comunicação